PENGARUH PEMOTONGAN TANGKAI METODE “CANGKEM BUAYA” TERHADAP PENINGKATAN KUALITAS TANDAN BUAH SEGAR - Aries Sukariawan; Muhammad Damara Damanik; Suroso Rahutomo (Institut Teknologi Sawit Indonesia (ITSI), 2019)
The low percentage fruit set will impact on the percentage of fruit to bunch and weight of Bunch. Fruit set islow causing the formation of partenokarpi fruit/coat so that the harvest process is involved in loading, carryingand processing. To solve the problem, the management of post-harvest Bunis is necessary. Comparing the